Assuring Customer Value, Customer Experience, and Trust to Improve Customer Loyalty - Indah Febriyanti; Meylani Tuti (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2023)
Consumer loyalty may be influenced by consumer trust. Consumer experience and customer value are only two of the many elements that contribute to consumer trust. Through consumer trust, this study seeks to examine the impact of customer value and customer experience on customer loyalty. Purposive sampling was the sampling method utilized, and 162 purchasers had made purchases more than twice. SmartPLS was used to conduct the analytical procedure utilizing structural equation modeling (SEM). According to the study's findings, trust and loyalty are influenced by both the customer experience and the value of the customer. Similarly, loyalty is influenced by the trust.